Development and validation of the health literacy assessment tool for older people in Taiwan: Potential impacts of cultural differences. Issue 2 (September 2015) - Chung, Min-Huey; Chen, Liang-Kung; Peng, Li-Ning; Chi, Mei-Ju
Highlights Culture of 'face' meant someone was embarrassed if he did not know how to do something. Existed health literacy assessment was hard for elderly because of culture of 'face'. Self-rated screening tool solved the difficulties for elderly to realize and answer existed tool. Elderly with no caregiver need for daily life had better health literacy performance.